Social Media as A Tool for Company-Customer Communication During a New Product Launch in The Pediatric Dietetics Industry - Kacper ROWIECKI; Jacqueline ROWIECKA (Communications of International Proceedings, 2022)
The process of communicating with the customer is a crucial marketing tool for modern companies. Through it, a company can gain a loyal, regular customer, develop its brand recognition and ultimately increase sales. Increasingly, social media is becoming a medium of constant contact between companies and their customers. The motive for raising the present issue was to investigate the degree of value for the potential customer of the activities carried out by influencers. There are not enough academic articles on this aspect. In view of the above, the authors states that the aim of this study is to assess the impact of marketing activities carried out by companies on social media on the purchasing decisions of their audience in the pediatric dietetics industry. Influencers of the topic of pediatric dietetics and their audiences were included in the field of empirical observation. At the level of analysis of their own empirical survey conducted on the basis of the author's questionnaire, the authors indicate the high value of using content marketing tools and the high impact of such activities on increasing sales and interest in the offer.
Keywords: e-marketing; content marketing; marketing strategy; paediatric dietetics